TECHNOLOGICALLY ADVANCED COMPANY: METHODOLOGICAL PROBLEMS OF STATUS DETERMINATION - O. A. Yeremchenko (Ekonomika Nauki)
The purpose of this study was to perform a survey of indicators and criteria on the basis of which foreign and Russian companies can be classified as technologically advanced and innovative. We compared the approaches used by international and domestic analytical companies to identify and rank technologically advanced companies, as well as lists of companies that ranked first in the various ratings of 2017–2018. A hypothesis was confirmed that there is no single methodologically valid approach to identifying high-tech companies in the world. It is shown that the lists of companies that are the leaders of global ratings of innovative companies in the world are weakly correlated and depend on the set of indicators used.